Superderivations and Jordan superderivations of generalized quaternion algebras - Leila Heidari Zadeh (Journal of Mahani Mathematical Research)
Let $H_{α,β}$ be the generalized quaternion algebra over a unitary commutative ring. This paper aims to consider superderivations and Jordan superderivations of $H_{α,β}$ and hence to obtain the superalgebra $Der_{s} (H_{α,β})$ of superderivations and $Der_{Js} (H_{α,β})$ of Jordan superderivations of $H_{α,β}$. It turns out that on generalized quaternion algebras, any superderivation is inner. In particular, there exist Jordan superderivations that are not superderivations.